1993
DOI: 10.1111/j.1600-079x.1993.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

One‐hour exposure to moderate illuminance (500 lux) shifts the human melatonin rhythm

Abstract: Salivary melatonin levels were measured in 12 healthy volunteers in order to determine whether a moderate light intensity, which suppresses the nocturnal rise of melatonin, was able to shift the melatonin rhythm. The samples were collected at 1-hr intervals under lighting of < 100 lux (experiment 1) or < 10 lux (experiment 2). The control melatonin profiles were determined during the first night. In the second night the subjects were exposed to light of 500 lux for 60 min during the rising phase of melatonin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…They further stated that their baseline melatonin onsets 'occurred around 22.00 h with remarkable reproducibility both within and across subjects', a finding that actually increases, rather than decreases the likelihood of masking, in that otherwise earlier onsets could have been artifactually delayed to 22.00 h due to light suppression. These authors dismissed the possibility of masking in their study by citing three studies, among others, in which baseline melatonin onsets measured under light intensities of less than 50 lx were also at 22.00 h. However, in one study [25], subjects slept until 07.30 or 08.00 h, not 07.00 h as in their study; in another study [26], sleep offset time was not specified, and in the third study [27] DLMOs were determined in saliva (which, for a given threshold, is always later than plasma DLMOs, since salivary levels are one-third those of plasma).…”
Section: Lewymentioning
confidence: 96%
“…They further stated that their baseline melatonin onsets 'occurred around 22.00 h with remarkable reproducibility both within and across subjects', a finding that actually increases, rather than decreases the likelihood of masking, in that otherwise earlier onsets could have been artifactually delayed to 22.00 h due to light suppression. These authors dismissed the possibility of masking in their study by citing three studies, among others, in which baseline melatonin onsets measured under light intensities of less than 50 lx were also at 22.00 h. However, in one study [25], subjects slept until 07.30 or 08.00 h, not 07.00 h as in their study; in another study [26], sleep offset time was not specified, and in the third study [27] DLMOs were determined in saliva (which, for a given threshold, is always later than plasma DLMOs, since salivary levels are one-third those of plasma).…”
Section: Lewymentioning
confidence: 96%
“…Recent studies have demonstrated that the human circadian pacemaker is more sensitive to light than originally determined by Lewy and colleagues [29]. Light intensities as low as 300 -500 lux (a metric measure of illuminance) when administered during the rising phase of the melatonin excretion have suppressed melatonin [36 -38] and delayed the melatonin rhythm [39]. Three 5-h pulses of indoor light intensity of about 180 lux, centred 1.5 h after the temperature minimum was able to induce a phase advance of the temperature and melatonin rhythms of 1.16 and 2.89 h, respectively [40 -42].…”
Section: Light Intensitymentioning
confidence: 99%
“…Studies have produced modest 30 min phase delays of the melatonin rhythm with a 1-h single light pulse [39,45]. Dawson and colleagues [46] were able to produce both phase delays and phase advances with a single 4-h light pulse of 12,000 lux.…”
Section: Light Durationmentioning
confidence: 99%
“…But a recent study emphasized the light-induced interruption of MT synthesis and the effect of MT circadian rhythm in humans [47]. Therefore we cannot ignore the influence of light, especially sunlight, and the revised times as shown in Fig.8 would have to be used.…”
Section: Differences Of Daylight Hoursmentioning
confidence: 99%